Transgender in Islamic Education: A Comparative Analysis of Buya Hamka and Amina Wadud's Thoughts - Maulana, Bintang; Astutik, Anita Puji (Al-Ulum: Jurnal Pendidikan Islam, 2025)
The transgender phenomenon has become a significant topic in global discussions on identity and human rights, prompting substantial debate among Muslims and challenging traditional interpretations of religious texts. This article examines the perspectives of two prominent Islamic intellectuals on the transgender issue. Buya Hamka, a conservative Indonesian cleric, adheres to a literal interpretation of the Quran and Hadith, considering gender change to be a violation of God's decree. In contrast, Amina Wadud, a progressive scholar from the United States, advocates a contextual interpretation that emphasises justice, humanity and acceptance of gender identity. The contrasting approaches of these two figures illustrate the diverse spectrum of Islamic thought, spanning from conservative to inclusive perspectives. This article not only discusses the theological and social implications of their views, but also highlights their relevance in the modern context. Through in-depth analysis, the article seeks to identify a middle ground that integrates respect for tradition with the need for justice and inclusiveness. This will provide valuable insights into how Islam can respond to transgender issues in the contemporary era.